2005
DOI: 10.1128/iai.73.8.4823-4833.2005
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Defensin Profiles inNeisseria gonorrhoeaeandChlamydia trachomatisUrethritis Reveal Novel Epithelial Cell-Neutrophil Interactions

Abstract: Defensins are key participants in mucosal innate defense. The varied antimicrobial activity and differential distribution of defensins at mucosal sites indicate that peptide repertoires are tailored to site-specific innate defense requirements. Nonetheless, few studies have investigated changes in peptide profiles and function after in vivo pathogen challenge. Here, we determined defensin profiles in urethral secretions of healthy men and men with Chlamydia trachomatis-and Neisseria gonorrhoeae-mediated urethr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
99
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(105 citation statements)
references
References 80 publications
3
99
1
Order By: Relevance
“…Conversely, Duits et al reported no effect of dexamethasone on hBD-1 or hBD-2 expression, whereas basal and induced hBD-3 mRNA expression was inhibited by dexamethasone in primary bronchial epithelial cells (16). Reasons for this discrepancy are not clear, but considering our finding that dexamethasone did not significantly affect the LPS-induced upregulation of LAP, it seems likely that expression of each ␤-defensin is regulated somewhat independently, as has been shown for their pathogen-specific induction in humans (34).…”
Section: Discussioncontrasting
confidence: 49%
“…Conversely, Duits et al reported no effect of dexamethasone on hBD-1 or hBD-2 expression, whereas basal and induced hBD-3 mRNA expression was inhibited by dexamethasone in primary bronchial epithelial cells (16). Reasons for this discrepancy are not clear, but considering our finding that dexamethasone did not significantly affect the LPS-induced upregulation of LAP, it seems likely that expression of each ␤-defensin is regulated somewhat independently, as has been shown for their pathogen-specific induction in humans (34).…”
Section: Discussioncontrasting
confidence: 49%
“…In Paneth cells, this processing is accomplished by tryptic digestion during or just after secretion into the intestinal lumen (55). A recent report has shown that, in the male urethra, HD-5 processing may depend on proteases secreted by neutrophils (50). Whether alternative HD-5 isoforms, other than the dominant tryptic form we have studied here, are active against papillomaviruses remains to be determined.…”
Section: Discussionmentioning
confidence: 90%
“…One report observed HD-5 peptide at various sites in the human female genital tract and found high ng͞ml levels of HD-5 in vaginal wash material (48). Other studies have reported HD-5 expression in the testes and male urethra, as well as in breast milk and keratinocytes of the oral and airway mucosa (49)(50)(51)(52)(53). In some of these studies, HD-5 expression appeared to correlate with local inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13] These antimicrobial polypeptides, some of which are induced in response to PAMP exposure, are effective at inhibiting Gram-positive and Gram-negative bacteria, fungi, and enveloped viruses, including Neisseria gonorrhoeae, Chlamydia trachomatis, Candida albicans, Herpes Simplex Virus-2, and Human Immunodeficiency Virus-1. [14][15][16][17][18][19][20][21][22][23] It is well known that estrogens, which act throughout the body, have both anti-inflammatory and proinflammatory functions. For example, E 2 enhances the production of proinflammatory interferon-γ and anti-inflammatory IL-10 in T cells.…”
Section: Introductionmentioning
confidence: 99%